Emerging assumptions and the future of artificial intelligence in teaching and learning processes in higher learning institutions in sub-Saharan Africa: A review of literature - Mwilongo, Kardo; Mwageni, Rhodes; Matto, George (Zambia journal of library & information science, 2024)
A research paper submitted to the Zambia journal of library & information science, Vol. 6, No. 2, of 2022: pg. 12-18